2017
DOI: 10.1016/j.celrep.2017.09.082
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged IKKβ Inhibition Improves Ongoing CTL Antitumor Responses by Incapacitating Regulatory T Cells

Abstract: Regulatory T cells (Tregs) prevent autoimmunity but limit antitumor immunity. The canonical NF-κB signaling pathway both activates immunity and promotes thymic Treg development. Here, we report that mature Tregs continue to require NF-κB signaling through IκB-kinase β (IKKβ) after thymic egress. Mice lacking IKKβ in mature Tregs developed scurfy-like immunopathology due to death of peripheral FoxP3 Tregs. Also, pharmacological IKKβ inhibition reduced Treg numbers in the circulation by ∼50% and downregulated Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 44 publications
(71 reference statements)
2
22
0
Order By: Relevance
“…In our experiments, deletion of NEMO inhibited canonical NF-kB pathway activation, whereas IKK-2 kinase deletion allowed canonical NF-kB activation, probably via NEMO-IKK-1 complexes or a further kinase so far not identified in our experiments. As shown in another of our publications, (21) mice lacking IKK-2 in mature T reg cells developed scurfylike immunopathology caused by the death of peripheral FoxP3 + T reg cells and pharmacological IKK-2 inhibition down-regulated FoxP3 and CD25 expression. In contrast, activated cytotoxic T lymphocytes were resistant to IKK-2 inhibition, because other pathways-in particular, nuclear factor of activated T cells-1 signaling.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In our experiments, deletion of NEMO inhibited canonical NF-kB pathway activation, whereas IKK-2 kinase deletion allowed canonical NF-kB activation, probably via NEMO-IKK-1 complexes or a further kinase so far not identified in our experiments. As shown in another of our publications, (21) mice lacking IKK-2 in mature T reg cells developed scurfylike immunopathology caused by the death of peripheral FoxP3 + T reg cells and pharmacological IKK-2 inhibition down-regulated FoxP3 and CD25 expression. In contrast, activated cytotoxic T lymphocytes were resistant to IKK-2 inhibition, because other pathways-in particular, nuclear factor of activated T cells-1 signaling.…”
Section: Discussionsupporting
confidence: 69%
“…A study published from our laboratory by Gotot et al (20) showed that systemic IKK-2 inhibition after the induction of the disease increased renal injury in the NTN model and that activated cytotoxic T lymphocytes were resistant to IKK-2 inhibition because of other pathways-in particular, nuclear factor of activated T-cell signaling (21). NF-kB activation was demonstrated by our group after ischemia-reperfusion kidney injury, and more Th17 cells were found in ischemic CD4xNEMO D mice but not in CD4xIKK2 D mice (22).…”
mentioning
confidence: 99%
“…As described earlier, patients with rare homozygous deletion of the IKBKB gene typically lack Treg cells [ 141 ]. Consistent with this, prolonged IKKβ inhibition was recently shown to partially deplete circulating FOXP3+ Treg cells, due to their dependence on NF-κB signalling for survival [ 198 ]. Consequently, administration of an IKKβ inhibitor after tumour vaccination in a mouse melanoma model enhanced the CTL-dependent anti-tumour response and delayed tumour growth, identifying IKKβ as a potential druggable immune checkpoint.…”
Section: Recent Therapeutic Opportunities To Target Ikkβmentioning
confidence: 64%
“…For example, genetic deletion of IKKβ in T-cells abrogated the anti-tumour response in mice with fibrosarcoma [ 199 ]. Indeed, Heuser et al observed that high doses of IKKβ inhibitor suppressed CTL responses in their model [ 198 ]. This dosage effect was explained by the fact that Tregs were more sensitive than CTLs to IKKβ inhibition due to a greater reliance on NF-κB signalling for survival.…”
Section: Recent Therapeutic Opportunities To Target Ikkβmentioning
confidence: 99%
“…It is well known that once T cells (CD3+) are activated to differentiate into cytotoxic T lymphocytes (CTLs, CD8+), they would secret IFN‐γ, granzyme, and so on to activate cell apoptosis pathway such as activating caspase‐3 to kill the tumor cells. Therefore, we collected the distant tumors in all the treated mice on day 36 to measure the tumor‐infiltrating CD3+CD8+ T cells and investigated the caspase‐3 expression within those tumors . For the blank control administrated with PBS, the tumors displayed a weak intensity of CD3+, CD8+, and caspase‐3+ signals, indicating the poor immune induction (Figure I,J; and Figures S13 and S14, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%